Clinical profile and outcome of diabetic foot ulcer, a view from tertiary care hospital in Semarang, Indonesia. Issue 1 (1st January 2017) - Pemayun, Tjokorda Gde Dalem; Naibaho, Ridho M.
ABSTRACT: Background : This study attempted to determine the disease burden in terms of clinical profile and outcome of diabetic foot ulcer (DFU) admissions at a tertiary care hospital in a developing country. Methods : In this descriptive study, the data were collected from the medical record of diabetic patients with foot ulcer who were treated in Dr. Kariadi General Hospital during a 3-year period. The demographic characteristic, type of foot lesion, etiology, isolated microorganism, treatment, and outcome were reviewed. Results : Foot problems accounted for 16.2% of total diabetic admission ( n = 1429). All patients had type 2 diabetes with no gender predominance. The mean age was 54.3 ± 8.6 years and diabetes control was very poor. Before admission, the ulcers had already developed for 4.7 ± 2.9 weeks; however, the majority of patients were unaware of the preceding causes. Ulcers were neuropathic in 42.2% of cases, neuroischemic in 29.9%, and pure ischemic at lesser percentage. More than 70% of ulcers were in Wagner grade ≥3 with infection event in nearly all patients. The most common isolates from culture were Gram-negative bacteria. A total of 98 (36.3%) lower extremity amputations (LEAs) at various level of the foot were carried out, including major LEA in 24 patients and multiple amputations in seven patients. Mortality rate due to DFU reached 10.7%. Conclusions: Diabetic foot problems constitute a source of morbidity, a reason for LEA surgery as well as being a cause of death among patients with diabetes mellitus.